Giorgio Tagliacozzo [8 de agosto de 1909 - 21 de noviembre de 1996]. (Una memoria) [pp. 11-20]. Trad. de José A. Marín. - Pinton, Giorgio A. (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 7-8 (1997). 495 págs. ISBN 1130-7498